Organic acid coated magnetic nanparticles as adsorbent for organic pollutants in aqueous solution. - Masuku, Makhosazana Nancy (My University, 2019)
Benzene, toluene and xylene (BTX) are water pollutants that appear very often in chemical and petrochemical wastewaters due to gasoline leakage from storage tanks and pipelines. These BTX compounds can cause adverse health effects on humans even at very low concentrations. Amongst the available pollutant removal methods from wastewater, adsorption has been used due to its ease of operation, simplicity and cost-effectiveness. Different adsorbents have been used for BTX removal, however the use of Magnetite-organic acid composites as an adsorbent seems to offer a much cheaper alternative. This work seeks to develop a one-step microwave synthesis and optimization of magnetite-oleic (MNP-OA) and magnetite-palmitic (MNP-PA) acid) composites. Response surface methodology was used to optimize the magnetite-organic acid composites. The optimum conditions estimated for MNP-OA acid composite were 78.3 % Fe content, 1561.9 S/cm conductivity, 82.2, 84.1, 85.3 mg/g for BTX adsorption capacity. The MNP-PA composite were 75.6 % Fe content, 1325.66 S/cm conductivity, 60.55, 64.47, 63.06 mg/g for BTX adsorption capacity. The materials were characterized, and the adsorption process was optimized for BTX removal from aqueous solution. X-ray analysis confirmed the formation of magnetite by the presence of both ferric and ferrous ion states on the surface. It was noted that after modification, the magnetite-organic acids characteristics peaks became broad and the height of the peaks decreased indicating that surface modification with organic acid controls the crystallinity of the material. The average cystalline size of MNP, MNP-OA, and MNP-PA composites were 19.7, 17.1 and 17.9 nm. FTIR analysis confirmed the target materials were produced and also to determine if the organic acids were imobilised on the surface of the magnetite. TEM images presented that the MNP, MNP-OA, and MNP-PA composites were spherical in shape with particle average sizes of 18.4 ± 0.5, 15.6 ± 0.5 and 16.5 ± 0.5 nm. The magnetite-organic acids show the particles with better isolated as compared to that of the MNP. The BET isotherms of the materials were described by a type IV characteristic related to uniform mesoporous materials. The magnetic saturation value for MNP, MNP-OA, and MNP-PA composites were 62.9, 59.0 and 51.0 emu/g. The decrease in magnetization was explained by the presence of the non-magnetic layer on magnetite surface. The pHpzc of MNP, MNP-OA, and MNP-PA composites were 6.9, 6.4 and 6.1. The decrease in pHpzc aftern modification was due to the charging acid-base interaction mechanism of metal oxide nanoparticles. The optimum pH for the adsorption of BTX onto MNP, MNP-OA, and MNP-PA composites was determined to be pH 7 for benzene, pH 8 for toluene and xylene. Among the three pollutants, xylene had the highest adsorption capacity followed by toluene and benzene. The optimum adsorbent dose for the adsorbents for the adsorption process was 0.1 g/dm3. The effect of time on the uptake of BTX onto MNP, MNP-OA, and MNP-PA composites show that initial adsorption of BTX occured between 0 and 3 min of contact time. The effect of initial concentration results shows the initial concentration of BTX increases from 100 to 350 mg/dm3 with an increase in adsorption capacity. The results suggest that the adsorption process is controlled by concentration driving force. The experimental data was fitted to the pseudo-first and pseudo-second-order kinetic models for all adsorbents and all pollutants. The pseudo-second-order models showed good correlation as compared to the first-pseudo model. Desorption studies for benzene, toluene and xylene using the pure magnetite, magnetite-palmitic and magnetite oleic acid composites indicate adsorption mrchanism can be explained in relation to acid–base chemistry. Electron donation from the phenyl ring of each benzene, toluene and xylene compound to surface iron atoms of magnetite has been suggested. The CH3OH and H2O desorbing agents were used and regeneration using five cycles show that the percentage desorption decreses from Benzene < Toluene < Xylene. The reduction in adsorption capacity after the cycles are attributed to decomposition of the adsorbents active sites and mass loss of the sample.
M. Tech. (Chemistry Department, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Benzene, toluene and xylene (BTX), mesoporous materials, petrochemical wastewaters, magnetite-organic acid; Dissertations, Academic.; Organic acids.; Nanoparticles -- Magnetic properties.; Organic water pollutants.